Work Life Balance and Employees’ Career Success: An Effect of Family Domain in Hospital in Kathmandu Valley - Manandhar, Sushma (PYC Nepal Journal of Management, 2012)
The paper provides empirical evidence on the relationship between the work life balance and employees’ career success in hospitals of Kathmandu valley. The structured questionnaire survey of 100 doctors and nurses was conducted from the two hospitals Tribhuvan University Teaching Hospital and B & B Hospital. The impacts of family domain variables on work life balance and employees’ career were studied in different dimensions. The descriptive research design, reliability analysis (Cronbach’s alpha), correlation and regression analysis were used as methods to observe and test the proposed hypotheses. The significant positive relation was found between work life balance and employees’ career success. The same result was found between work life balance and employees’ career success with working spouse. But the study showed the negative effects of parental demand on work life balance and employees’ career success.